DDRE-28. MECHANISTIC AND THERAPEUTIC LINKS BETWEEN PURINE BIOSYNTHESIS AND DNA DAMAGE IN GLIOBLASTOMA. (25th March 2021) - Scott, Andrew; Zhou, Weihua; Wilder-Romans, Kari; Feng, Jiane; Wu, Zhe; Andren, Anthony; Zhang, Li; Sajjakulnukit, Peter; Kachman, Maureen; Umemura, Yoshie; Schmitt, Melanie; Qi, Nathan; et al.
Abstract: Glioblastoma (GBM) is the most common and aggressive adult brain cancer. Radiation therapy (RT) is a critical treatment modality, and development of RT resistance is the predominant cause of recurrence and mortality in GBM patients. Using cell line models as well as patient-derived xenografts and neurospheres in orthotopic brain tumor models, we have identified increased rates and dependence upon de novo purine biosynthesis as a hallmark of GBM RT resistance. More recently, we have discovered that radiation treatment acutely stimulates flux through de novo purine synthesis in cell line and neurosphere models of GBM. This RT-induced increase in de novo purine synthesis is dependent on signaling through the DNA damage response and thus appears to be an adaptive mechanism to supply purines to repair radiation-induced DNA damage. To determine whether this regulatory mechanism also exists in vivo, we have used advanced metabolomic and metabolic tracing techniques with 13 C-labeled glucose and 15 N-labeled glutamine in mice bearing RT-resistant GBM patient-derived orthotopic brain tumors. We found that that orthotopic GBM PDXs had elevated activity of de novo purine synthesis that increased further after RT, while normal cortex had little activity even after RT. These observations have therapeutic relevance, as targeting this metabolic pathway with the FDA-approved purine biosynthesis inhibitor mycophenolate mofetil (MMF) overcomes GBM radiation resistance in mouse models in vivo . The lack of de novo purine synthesis in normal cortex suggests that targeting this pathway may be tumor specific. Collectively our data suggest that de novo synthesis of purines mediates RT resistance in GBM and that treatment of brain tumors with MMF in combination with RT may be a promising therapeutic strategy in patients.